(untitled) (Economic Journal of Development Issues, 2012)
India had a strong cultural emphasis on education both at private and government level. Since 1990s, government spending on education has been growing at 12% a year, of which roughly a fifth goes towards higher education. By 2030, share of skilled labour in working population will be just 6.2% compared to 14% for world as a whole and 40% in high income countries. While India has made rapid strides in expanding higher education systems, she still faces a number of challenges in terms of effectively utilizing existing supply of talent as well as increasing it sufficiently to meet demands of rapidly growing economy. How to leverage expertise and knowledge of Diasporas for benefit of India is main issue the paper addresses and emphasizes beginning of a new agenda of promoting policy reform and institutional innovation in collaboration with Diasporas networks, which can be crucial bridges between policy, technological and managerial expertise and local scenarios. The public policy reform, educational innovations and promotion of a knowledge-based private sector are few areas where Diasporas members could team up with local governments and external funding agencies to tap Indian talents and promote equitable development. DOI: http://dx.doi.org/10.3126/ejdi.v13i0.7195 Economic Journal of Development Issues Vol.13 & 14 2011, pp.15-33